Penguatan Nilai-Nilai Tasawuf Sebagai Strategi Menjaga Keseimbangan Spiritual Dan Sosial Terhadap Mahasiswa S1 Fakultas Tekhnik Sipil : Penguatan Nilai-Nilai Tasawuf Sebagai Strategi Menjaga Keseimbangan Spiritual Dan Sosial Terhadap Mahasiswa S1 Fakultas Tekhnik Sipil - Moh Muntholib; Sholchan Ghozali (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
The era of rapid globalization and technological advancement has significantly impacted the social and spiritual lives of university students, including those from engineering disciplines. Civil engineering students often face academic pressure and a competitive modern lifestyle, which leads to the neglect of their spiritual well-being. This study aims to strengthen Sufi (tasawuf) values as a strategy to maintain students’ spiritual and social balance through a Participatory Action Research (PAR) approach. The intervention was implemented in the form of microteaching by postgraduate students of Sunan Giri University to undergraduate students of the Faculty of Civil Engineering. The findings indicate that tasawuf values such as sincerity (ikhlas), patience (sabr), asceticism (zuhud), and self-reflection (muhasabah) can be understood and internalized by engineering students in a contextual and practical manner. The positive responses from participants suggest that tasawuf serves as a rational and relevant spiritual solution to the challenges of modern life. The study also highlights that participatory approaches encourage deeper self-reflection and value transformation.